MANAGEMENT OF DYSTOCIA FOLLOWED BY UTERINE PROLAPSE IN MARES -A REPORT OF TWO CASES - HADIYA, K K; PARMAR, J J; DHAMI, A J; PATEL, J A; SHAH, A I (The Indian Journal of Animal Reproduction, 2023)
This communication puts on record the successful clinical management of dystocia due to stress induced abortion in one mare and uterine inertia with overdue gestation in another using oxytocin and digitally induced cervical dilation and forced extraction of fetus followed by uterine prolapse a few hours later in both the mares and their medical management.